Effect of Qris Digital Payments (Quick Response Code In-donesian Standard) On Students' Consumptive Behavior Madiun State Polytechnic - Muh. Supriyanto; Rino Desanto Wiwoho; Srimiatun Srimiatun (Lembaga Pengembangan Kinerja Dosen, 2025)
QRIS digital payment is a payment system via a QR code that users use when making a transaction. Digital payments that offer convenience for users do not always have a positive impact, but there are also negative impacts, one of which is consumer behavior. Consumptive behavior occurs due to the individual's tendency to buy things unplanned to fulfill desires without careful consideration in order to achieve satisfaction. The aim of this research is to determine the effect of QRIS digital payments on the consumer behavior of Madiun State Polytechnic students. This research uses quantitative methods with a type of causal research. The indicators used in this research include 5 indicators of digital payments according to Gosal and Linawati (2018) and 6 indicators of consumer behavior according to Sumartono 2002. The data collection technique used was a questionnaire with a sample of 97 people selected using purposive sampling. Instrument testing carried out includes validity tests, reliability tests and normality tests. The analytical method used is simple linear regression analysis and hypothesis testing using the t test. Data processing in the research was carried out using Microsoft Excel and SPSS. The research results show that QRIS digital payments influence consumer behavior with a significance value of 0.000. The ability of the QRIS digital payment variable to explain consumer behavior variables is 34.4% and the correlation value is 0.587.